ANALISIS KETERAMPILAN PENGOPERASIAN PROGRAM MYOB PADA SISWA KELAS XI AK DI SMKN 3 PONTIANAK - Herdiyanti, Lina; Genjik, Bambang; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract Computer accounting is one of the productive subjects in vocational schools. One application that is used is MYOB (Mind Your Own Business). The general problem that was tried to be raised in this study was